Effect of Squeeze Casting Parameter Process ( Melt Temperature, Die Temperature And Al-3,22%Si ) On Microstructure, Hardness And Tensile Strength In Thin Wall Casting - Aspiyansyah Aspiyansyah (Fakultas Teknik UM Pontianak, 2010)
px;